Piper umbellatum L. (Piperaceae): Phytochemical profiles of the hydroethanolic leaf extract and intestinal anti-inflammatory mechanisms on 2, 4, 6 trinitrobenzene sulfonic acid induced ulcerative colitis in rats. (23rd May 2020) - Arunachalam, Karuppusamy; Damazo, Amilcar Sabino; Macho, Antonio; Lima, Joaquim Corsino da Silva; Pavan, Eduarda; Figueiredo, Fabiana de Freitas; Oliveira, Darley Maria; Cechinel-Filho, Valdir; Wagner, Theodoro Marcel; Martins, Domingos Tabajara de Oliveira
Abstract: Ethnopharmacological relevance: Piper umbellatum L. leaves, commonly found in the Amazon, Cerrado and Atlantic rain forest regions of Brazil, are widely used as a traditional medicine to treat gastrointestinal disorders and inflammation, among others diseases. Also, previous scientific studies demonstrated that P. umbellatum has gastroprotective and anti-inflammatory activity. Aim: To investigate the phytochemical profiles and the intestinal anti-inflammatory effect of the hydroethanolic extract of P. umbellatum (HEPu) leaf on ulcerative colitis in rats. Materials and methods: In this study, the chemical composition of HEPu was analyzed by gas chromatography-mass spectrometry (GC-MS) and liquid chromatography coupled to mass spectrometry (LC/MS). Also, this work studied the effects of HEPu on ulcerative colitis induced by 2, 4, 6-trinitrobenzene sulfonic acid (TNBS, 30 mg/mL in 20% ethanol) by intrarectal administration in rats. Simultaneously, animals were pre-treated orally with HEPu (30, 100 and 300 mg/kg), mesalazine (500 mg/kg), or vehicle. At the end of the experimental period, clinical signs of ulcerative colitis were evaluated by determination of weight loss, gross appearance, ulcer area and histological changes. Reduced glutathione (GSH), lipoperoxides (MDA) and nitric oxide (NO) levels, and superoxide dismutase (SOD), myeloperoxidase (MPO) and catalase (CAT) activities were determined in colon tissues. Also, pro-inflammatory mediators such as tumor necrosis factor alpha (TNF-α) and interleukin 1 beta (IL- 1β) were quantified by immunoassay on the surface of fluorescent-coded magnetic beads (Luminex MagPix System). Results: GC-MS analysis showed the presence of 17 different phytochemical compounds in the HEPu. LC/MS analyses revealed the presence of compounds in HEPu as protocatechuic acid, ferulic acid, kaempferol, rosmarinic acid, apigenin and ursolic acid. Treatment with HEPu significantly ameliorated weight loss, macroscopic damage, ulcerated area and histopathological changes such as sub-mucosal edema, cell infiltration, ulceration and necrosis ( p  < 0.001). Furthermore, HEPu (30, 100, and 300 mg/kg, p.o) inhibited the levels of oxidative parameters, such as MPO (49%, 53%, and 62%, p  < 0.001), NO (20%, 19%, 22%, p  < 0.01), and MDA (75%, 83%, 70%, p  < 0.001), whereas increased the antioxidant activities such as SOD (208%, 192%, 64%, p  < 0.001), GSH (94%, 75%, 49%, p  < 0.01), and CAT (92%, 69%, 108%, p  < 0.01). The extract also inhibited the pro-inflammatory cytokines TNF-α (81%, 85%, 85%, p  < 0.001) and IL-1β (95%, 79%, 89%, p  < 0.001) levels. Conclusion: Together, these results revealed that P. umbellatum L. is a promising source of metabolites to be used in the treatment of inflammatory bowel disease. Graphical abstract: Image 1